2018
DOI: 10.1186/s12957-018-1459-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of primary giant cell tumor of bone after curettage with or without perioperative denosumab in Japan: from a questionnaire for JCOG 1610 study

Abstract: BackgroundGiant cell tumor of bone (GCTB) is an intermediate tumor known to be locally aggressive, but rarely metastasizing. To plan a prospective study of GCTB, we performed a questionnaire survey for institutions participating in the Bone and Soft Tissue Tumor Study Group (BSTTSG) in the Japan Clinical Oncology Group (JCOG) in 2015.MethodsWe reviewed 158 consecutive patients with primary GCTB treated with curettage without perioperative denosumab from 2008 to 2010 in Japan. We investigated local and distant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 24 publications
0
55
0
2
Order By: Relevance
“…Based on the Campanacci classification, which has been widely accepted in evaluating giant cell tumor, grade III represented the aggressive type. A series of studies reported Campanacci grade III as the risk factor for tumor recurrence [19,20] and lung metastasis [21,22]. The recurrence was also reported to be a risk factor for resulting in metastasis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Campanacci classification, which has been widely accepted in evaluating giant cell tumor, grade III represented the aggressive type. A series of studies reported Campanacci grade III as the risk factor for tumor recurrence [19,20] and lung metastasis [21,22]. The recurrence was also reported to be a risk factor for resulting in metastasis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The total dosage given prior to surgery was inconsistent among included studies. Four studies [13,[15][16][17] administered denosumab pre-operatively and post-operatively. Overall, 61 cases in the denosumab group and 175 cases in the control group had local recurrence.…”
Section: Recurrencementioning
confidence: 99%
“…1.16 to 4.85, p=0.02, I 2 =57%)(figure2) . Surgical choice was taken into account by comparing cases underwent curettage with denosumab and curettage alone in 4 studies [9,[16][17][18](OR: 2.13, 95% CI: 0.95 to 4.76, p=0.07, I 2 =29%)( Figure 3), though the result was not statistically significant. 7 studies [9,[15][16][17][18][19][20] reported outcome on primary lesions, which also suggest significantly higher risk of local recurrence in the denosumab group(OR: 1.91, 95% CI: 1.17 to 3.09, p=0.009, I 2 =36%)( Figure 4).…”
Section: Recurrencementioning
confidence: 99%
“…In 4 studies [13,[15][16][17] denosumab was administered both preoperatively and postoperatively, no statistically significant difference was found when comparing pre and post denosumab administration group and control group in terms of local recurrence(OR: 1.96, 95% CI: 0.63 to 6.07, p=0.24, I 2 =79%) ( Figure 5).…”
Section: Recurrencementioning
confidence: 99%
See 1 more Smart Citation